Pemberdayaan Potensi Alam Pesisir Pantai Melalui Pelatihan Penataan Wisata Alam Di Desa Molosipat Kabupaten Pohuwato Provinsi Gorontalo - Kalih Trumansyahjaya; Abdi Gunawan Djafar; Niniek Pratiwi (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2019)
Indonesia is a maritime country with great potential, in various aspects of living natural resources and human resources. Not many people know that Gorontalo is a province that has amazing coastal tourism objects. Since becoming a province, Gorontalo has explored a lot of potential so that it can compete ahead with other provinces, especially in the field of natural tourism. Talking about the potential for natural tourism, in Gorontalo Province, especially Molosipat Village, Pohuwato Regency has several coastal areas with beautiful natural potential so that it is very suitable to be used as a beach tourism spot. The large number of natural potentials in Molosipat village is not followed by a good arrangement of the tourist area so that the natural potential is simply lost to tourists. In connection with these conditions, the focus in the implementation of this service is to provide socialization and training to the community of Molosipat village related to how to organize natural tourism in empowering the natural potential of the coast which is owned by the Molosipat coastal area. This activity is carried out by providing socialization and training which includes: discourse, discussions and structuring the Molosipat beach tourism area. The targets that will be involved in this activity are the Molosipat community, especially those in the Molosipat beach hamlet, youth organizations and Molosipat village officials. The implementation of the "Kuliah Kerja Nyata (KKN) Tematik" service activity held in Molosipat Village, Popayato Barat Subdistrict, Pohuwato Regency has been running according to the initial plan, but in the process of implementing it still needs to be done regularly in training and mentoring because this will be useful in developing structuring beach tourism area in the village of Molosipat. Therefore, the form of community service activities in terms of socialization and training on structuring coastal tourism areas to empower the natural potential of the coast should be continued continuously.